Robust real-time IEEE802.15.4 MAC protocol in multi-hop mesh network for distribution smart grid-AMI - Shabani, Hikma; Ahmed, Musse Mohamud; Khan, Sheroz; Hameed, Shihab A.; Habaebi, Mohamed Hadi (International Journals of Engineering and Science (IJENS), 2013)
The success of Smart Grid will be based on grid-integrated real-time communication between various grid elements in generation, transmission, distribution and loads. Merit to the ZigBee/IEEE802.15.4std low cost, low power, low data rate, short range, simplicity and free licensed spectrum that makes wireless sensor networks (WSNs) the most suitable wireless technology for smart grid applications. This paper focuses at the distribution layer from advanced metering infrastructure (AMI) gateways at the consumer premises to the distribution point where a multi-hop mesh network is built for large coverage data exchange. While beacon-enabled mode is adopted for energy efficient operations, IEEE802.15.4std does not define any mechanisms to enable beacon mode in mesh network. Therefore, in this paper, a modified Zigbee WSN MAC protocol for real-time multi-hop mesh network topology is developed. The protocol performance is evaluated using NS-2 simulation and the preliminary results are encouraging.